Mad men. Season four [videorecording (DVD)] - Weiner, Matthew; Abraham, Phil; Uppendahl, Michael; Hamm, Jon, 1971-; Jones, January, 1978-; Slattery, John, 1962-; Moss, Elisabeth, 1982-; Hendricks, Christina, 1975-; Kartheiser, Vincent, 1979- (Lionsgate, 2010)
Set in 1960s New York City, Mad Men explores the glamorous and ego-driven 'Golden Age' of advertising, where everyone is selling something and nothing is ever what it seems. Welcome to a Mad New World. Returns for a new year rife with possibilities. Last season stunned fans with its cliffhanger finale, as Don Draper's professional and personal lives unexpectedly imploded.